2012
DOI: 10.1590/s0100-54052012000100011
|View full text |Cite
|
Sign up to set email alerts
|

Metodologias para obtenção de resistência e/ou tolerância da soja à ferrugem-asiática

Abstract: RESUMOOs objetivos deste tra balho foram complementar os estudos dos mecanismos genéticos da resistência e tolerância da soja à ferrugemasiática e su gerir metodologias de melho ra me nto qu e perm ita m o a c ú mu lo de gen es ma ior es e m eno res. S eis ex pe rim ent os for a m r ea li za d os d u r a nt e t rê s sa fra s em Lo nd ri n a , P R , de 2 0 0 5 /0 6 a 2 0 0 7/0 8 , envolvendo cinco pa renta is e a s gerações deriva das Palavras-chave adicionais: Phakopsora pachyrhizi, Glycine Max, métodos de mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
1
Order By: Relevance
“…Variables for NP4 and SMP were similar for all genotypes studied. Findings different from the research by Lima et al (2012), who observed distinctions in SMP between parents, F2 and F3 generations. Families IRC3_159, IRC16_82, IRC19_62, and IRC36_152 satisfied the highest means for first pod insertion height (FPI), plant height (PH), and number of pods on main stem (NPS), whereas IRC1_194 satisfied the means for the number of pods on branches (NPB), number of branches (NBR), number of pods with 1 grain (NP1), number of pods with 2 grains (NP2) and number of pods with 3 grains (NP3) (Table 3).…”
Section: Resultscontrasting
confidence: 99%
“…Variables for NP4 and SMP were similar for all genotypes studied. Findings different from the research by Lima et al (2012), who observed distinctions in SMP between parents, F2 and F3 generations. Families IRC3_159, IRC16_82, IRC19_62, and IRC36_152 satisfied the highest means for first pod insertion height (FPI), plant height (PH), and number of pods on main stem (NPS), whereas IRC1_194 satisfied the means for the number of pods on branches (NPB), number of branches (NBR), number of pods with 1 grain (NP1), number of pods with 2 grains (NP2) and number of pods with 3 grains (NP3) (Table 3).…”
Section: Resultscontrasting
confidence: 99%